Dual microbial inoculation for tripartite benefits: soybean biomass enhancement, root rot control and chlorothalonil residue reduction - Jie, Weiguang; Zhang, Min; Tan, Yiwen; Yang, Haobo; Wang, Wenkai; Kan, Lianbao (Frontiers in Plant Science, 2025)
As global agriculture shifts toward an ecological civilization model, microbial fertilizers have emerged as a new strategy to promote plant growth and enhance soil fertility. In this study, the effects of Rhizophagus intraradices and Acinetobacter calcoaceticus on soybean biomass, root rot disease index, chlorothalonil residue in soybean rhizosphere soil and grains, and the composition of the bacterial community in the rhizosphere soil were investigated through pot experiments. Soybean biomass, chlorothalonil residue and bacterial community were analyzed by direct measurement method, gas chromatographic method and high throughput sequencing, respectively. The findings demonstrated that in the R. intraradices and A. calcoaceticus inoculation group, AMF spore density and colonization rate increased by 116.42% and 139.17%, respectively, compared to the control group. Microbial inoculum significantly enhanced the soybean biomass. Compared with the control group, the hundred-grain weight in the R. intraradices and A. calcoaceticus inoculation group increased by 35.46%. The disease index of soybean root rot decreased by 77.78% in the R. intraradices and A. calcoaceticus inoculation group relative to the control group. Furthermore, compared with the chlorothalonil-treated group, the chlorothalonil residue in both the rhizosphere soil and soybean grains in the chlorothalonil-treated and inoculated with R. intraradices and A. calcoaceticus group decreased by 80.02% and 81.65%, respectively. Additionally, microbial inoculum and chlorothalonil application exerted substantial effects on the composition of the bacterial community. Specifically, co-inoculation with R. intraradices and A. calcoaceticus led to an increase in the relative abundance of Acidobacteriota and Patescibacteria in the rhizosphere soil. Conversely, chlorothalonil application resulted in a reduction in the relative abundance of these bacterial taxa. The primary objective of this study was to provide theoretical support for the application of microbial inoculum as a strategy to mitigate soybean root rot, enhance growth, and reduce pesticide residue, thereby contributing to sustainable agricultural practices.